8-Oxo-2’-deoxyguanosine – biomarker of the oxidative stress - T. S. Nevredimova; N. V. Marmiy; D. S. Esipov; O. V. Esipova; V. I. Shvets (Тонкие химические технологии, 2014)
Free radical mechanism of a cell damage is one of the universal non-specific pathogenic pathways in a cause of many diseases, including cancer, neurodegenerative diseases, atherosclerosis and aging. So in nuclear and mitochondrial DNA, guanine hydroxylation to 8-position gives 8hydroxy2'deoxyguanosine (8OHdG) and 8oxo7,8dihydro2'deoxyguanosine (8oxodG). These substances are one of the predominant products of free radicalinduced oxidative damages. They are usually been applied as biomarkers of oxidative stress and carcinogenesis. The direct oxidation of guanine or incorrect inclusion of 8-oxo-dGTP from the nucleotide pool by polymerases, lead to a lack of specificity of the base pairing in DNA, favoring mutagenesis. Firstly 8-oxo-dG has been described by H. Kasai and S. Nishimura in 1983. Since then, this damage has been widely measured in various tissues and body fluids as blood, urine, brain, liver, and others. Today 8-oxo-dG is already used not only as a marker of oxidative stress, but also as a tool for prognosis of diseases and results of applied therapy. Now many efforts are focused on developing the procedure of measurement of 8-oxo-dG content in tissues and body fluids. In this paper we also discuss the role of the 8-oxo-dG as a biomarker of oxidative stress and a predictor of diseases and results of the applied therapy.